Tests of adrenal insufficiency. Issue 4 (1st April 1999) - Agwu, J C; Spoudeas, H; Hindmarsh, P C; Pringle, P J; Brook, C G D
Abstract : AIM: In suspected adrenal insufficiency, the ideal test for assessing the hypothalamo–pituitary–adrenal axis is controversial. Therefore, three tests were compared in patients presenting with symptoms suggestive of adrenal insufficiency. METHOD: Responses to the standard short Synacthen test (SSST), the low dose Synacthen test (LDST), and the 08:00 hour serum cortisol concentration were measured in 32 patients. A normal response to the synacthen test was defined as a peak serum cortisol of ⩾ 500 nmol/l and/or incremental concentration of ⩾ 200 nmol/l. The sensitivity and specificity of the 08:00 hour serum cortisol concentration compared with other tests was calculated. RESULTS: Three patients had neither an adequate peak nor increment after the SSST and LDST. All had a serum 08:00 hour cortisol concentration of < 200 nmol/l. Eight patients had abnormal responses by both criteria to the LDST but had normal responses to the SSST. Three reported amelioration of their symptoms on hydrocortisone replacement. Twenty one patients had a normal response to both tests (of these, 14 achieved adequate peak and increment after both tests and seven did not have an adequate peak after the LDST but had a normal increment). The lowest 08:00 hour serum cortisol concentration above which patients achieved normal responses to both the LDST and SSST was 500 nmol/l. At this cut off value (compared with the LDST), the serum 08:00 hour cortisol concentration had a sensitivity of 100% but specificity was only 33%. CONCLUSION: The LDST revealed mild degrees of adrenal insufficiency not detected by the SSST. The value of a single 08:00 hour serum cortisol concentration is limited.